Positive and negative cooperativity of TNF and Interferon-γ in regulating synovial fibroblast function and B cell survival in fibroblast/B cell co-cultures - Lowin, Torsten (Sci Rep, 2020)
Synovial fibroblasts (SF) were reported to produce B cell activating factor (BAFF) in response to stimulation with interferon-γ (IFN-γ) or tumor necrosis factor (TNF). However, the influence of these pro-inflammatory cytokines on other receptors/ligands of the TNF superfamily or associated cytokine receptors in SF has not been investigated yet. Here we show the differential regulation of BAFF (CD257), Fn14 (CD266), TACI (CD267), BAFF-R (CD268), BCMA (CD269), CD40 ligand (CD40L, CD154), IFN-γR (CD119), Leptin receptor (ObR, CD295), VCAM-1 (CD106) and membrane TGF-β in isolated SF and the impact of IFN-γ/TNF co-incubation on proliferation, IL-6 and IL-8 production. In addition, the impact of differentially stimulated SF on B cell survival in co-cultures was assessed. Surface cytokines and cytokine receptors were detected by flow cytometry. Soluble cytokine receptors and cytokines were quantified by ELISA. Proliferation was assessed by cell titer blue. Murine B cell survival in fibroblast/ B cell co-cultures was determined by annexin V/propidium iodide staining and flow cytometry. IFN-γ together with TNF synergistically and significantly increased the cell surface levels of BAFF, Fn14, TACI, BAFF-R, BCMA, CD40L, ObR and IFN-γR in rheumatoid arthritis SF after 72 h incubation. Soluble BAFF was only induced by IFN-γ and inhibited by TNF. Addition of TWEAK had no influence on proliferation or IL-8 production but decreased TNF-induced IL-6 production, whereas APRIL, BAFF and leptin did not modulate TNF or TNF/IFN-γ-induced proliferation or cytokine production. Proliferation was increased by TNF and further enhanced by the addition of IFN-γ. In co-culture experiments, SF stimulated with TNF/IFN but not TNF or IFN-γ alone increased shedding of VCAM-1 and expression of membrane TGFβ, which was associated with reduced survival of murine B cells. IFN-γ and TNF regulate the expression of TNF family member cytokines and associated receptors. Ligation of IFN-γR and Fn14 under pro-inflammatory conditions modulated IL-6/IL-8 production and proliferation. In B cell/SF co-cultures, the combination of TNF/IFN reduced B cell survival possibly via enhanced VCAM-1 shedding and/or increased TGF-β production. IFN-γ is necessary for the observed effects on B cell survival and SF cytokine production and emphasizes its anti-inflammatory role in rheumatoid arthritis.